Cina Benteng: The Latest Generations and Acculturation - Setiawan, Billy Nathan (Lingua Cultura, 2015)
The aim of this paper was to investigate the acculturation process encountered by the two latest generations of Cina Benteng. A Skype interview was conducted with two young Cina Benteng descents. The analysis was also supported by insightful remark from the parents of the two interviewees. This study discovers that the two generations seem to respond to the acculturation process in different ways. However, although some traditions are no longer relevant to the later generation, their identity as a Chinese descent cannot be easily removed.